Les îles de Polynésie française face à l’aléa cyclonique - Sébastien Larrue; Thomas Chiron (VertigO)
Using retrospective analysis with Geographic Information System methodology (GIS, Mapinfo® Professional version 7.0), the aim of this paper is to contribute to a better understanding of cyclone hazard and cyclone tracks in French Polynesia. The GIS database on cyclones was compiled from non-meteorological sources of information, many in the territorial archives of Papeari (Tahiti Island), and meteorological reports. The major meteorological sources used in this paper were the data of Meteo-France French Polynesia and two cyclone databases : (1) the U.S. Naval Pacific Meteorology and Oceanography Center via the Joint Typhoon Warning Center (2005) and the Tropical Cyclone Best-Tracks interface, and (2) the Australian Severe Weather site. On the French Polynesia map in projection WGS 1984, the cyclone tracks of the disturbances were imported and digitized with GIS Mapinfo. The uncertainty concerning the reliability of the data and the cyclone tracks before 1970 restricted our study to the 1970-2009 period. The cyclone track pattern between 1970 and 2009 was identified, showing a “conical shape” between the Society Islands and the Austral Islands where 70 % of the cyclone tracks were observed. The map shows that the islands most at risk from cyclones are the west coasts of the Society Islands and the east coasts of Austral Islands. Recently, cyclone Oli (February 4th, 2010) and his track in the middle of the “conical shape” located in the vinciny of the Society Islands and the Austral archipelago strengthen this trend.